2009
DOI: 10.1007/s10236-009-0237-y
|View full text |Cite
|
Sign up to set email alerts
|

Sediment-induced buoyancy destruction and drag reduction in estuaries

Abstract: This paper presents an analysis of drag reduction by buoyancy destruction in sediment-laden open channel flow. We start from the log-linear profile proposed by Barenblatt (Prikladnaja Matematika i Mekhanika, 17:261-274, 1953), extended with a second length scale to account for free surface effects. Upon analytical integration over the water depth, an expression for sediment-induced drag reduction is found in terms of an effective Chézy number, water depth, bulk Richardson number, and Rouse number. This relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 21 publications
7
47
0
Order By: Relevance
“…Even in the downstream part (GQ150), values of 6-8 g/l are measured. This is more than sufficient for reducing the effective hydraulic drag (Winterwerp et al 2009;Winterwerp and Wang 2013;Winterwerp et al 2013). It is noted that in November 2007, a short high river discharge event occurred.…”
Section: Suspended Sediment and Effective Hydraulic Dragmentioning
confidence: 93%
See 2 more Smart Citations
“…Even in the downstream part (GQ150), values of 6-8 g/l are measured. This is more than sufficient for reducing the effective hydraulic drag (Winterwerp et al 2009;Winterwerp and Wang 2013;Winterwerp et al 2013). It is noted that in November 2007, a short high river discharge event occurred.…”
Section: Suspended Sediment and Effective Hydraulic Dragmentioning
confidence: 93%
“…Therefore, it is concluded that the anomalous behaviour of the estuary with high tidal amplification is most likely caused by reduction of effective hydraulic drag in those periods. Winterwerp et al (2009) give the following relation for the effective Chézy coefficient as function of the distribution of suspended sediment concentration: Fig. 11 Comparison between numerical model results and field data concerning the relation between the amplification factor and the tidal amplitude …”
Section: November 2007mentioning
confidence: 98%
See 1 more Smart Citation
“…This may require a vertical resolution as low as several mm, and therefore a large number of grid cells-the resulting computational time of the model may become very long. A second option is to relate the bed roughness to suspended sediment concentration using expressions such as derived by Winterwerp et al (2009). A third option is to strengthen the effect of sediment on hydrodynamics through a modified Prandtl-Schmidt number σ t .…”
Section: Hydraulic Dragmentioning
confidence: 99%
“…1DV has been attempted to study the fine (cohesive) sediment transport within the Changjiang River estuary (Shi 2001). Other relevant numerical modeling studies have been attempted since 1988 (Zhao et al 1988;Port and Delta Consortium Ltd 1995;Zhou and Wu 1996;Dou et al 1999;Zhu et al 1999;Zhou et al 2000;van Rijn 2007;Hu et al 2009;and Winterwerp et al 2009). Despite the studies listed above, a couple of fundamental issues relating to the complex processes, i.e., resuspension/erosion, flocculation/settling, and deposition, which occur within the Changjiang River estuary, still remain unanswered.…”
Section: Introductionmentioning
confidence: 98%